Identification and Characterization of a Mucilaginibacter sp. Strain QM49 β-Glucosidase and Its Use in the Production of the Pharmaceutically Active Minor Ginsenosides (S)-Rh(1) and (S)-Rg(2) - Cui, Chang-Hao (American Society for Microbiology, 2013)
Here, we isolated and characterized a new ginsenoside-transforming β-glucosidase (BglQM) from Mucilaginibacter sp. strain QM49 that shows biotransformation activity for various major ginsenosides. The gene responsible for this activity, bglQM, consists of 2,346 bp and is predicted to encode 781 amino acid residues. This enzyme has a molecular mass of 85.6 kDa. Sequence analysis of BglQM revealed that it could be classified into glycoside hydrolase family 3. The enzyme was overexpressed in Escherichia coli BL21(DE3) using a maltose binding protein (MBP)-fused pMAL-c2x vector system containing the tobacco etch virus (TEV) proteolytic cleavage site. Overexpressed recombinant BglQM could efficiently transform the protopanaxatriol-type ginsenosides Re and Rg(1) into (S)-Rg(2) and (S)-Rh(1), respectively, by hydrolyzing one glucose moiety attached to the C-20 position at pH 8.0 and 30°C. The K(m) values for p-nitrophenyl-β-d-glucopyranoside, Re, and Rg(1) were 37.0 ± 0.4 μM and 3.22 ± 0.15 and 1.48 ± 0.09 mM, respectively, and the V(max) values were 33.4 ± 0.6 μmol min(−1) mg(−1) of protein and 19.2 ± 0.2 and 28.8 ± 0.27 nmol min(−1) mg(−1) of protein, respectively. A crude protopanaxatriol-type ginsenoside mixture (PPTGM) was treated with BglQM, followed by silica column purification, to produce (S)-Rh(1) and (S)-Rg(2) at chromatographic purities of 98% ± 0.5% and 97% ± 1.2%, respectively. This is the first report of gram-scale production of (S)-Rh(1) and (S)-Rg(2) from PPTGM using a novel ginsenoside-transforming β-glucosidase of glycoside hydrolase family 3.